Apakah Good Corporate Governance Perspektif dan Corporate Social Responbility Indeks Berpengaruh Terhadap Kinerja Keuangan? - Anandita Zulia Putri; Ningrum Pramudiati (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of the implementation of Good Corporate Governance perspective and Corporate Social Responsibility on financial performance in mining sector companies listed on the Indonesia Stock Exchange in 2015-2018. Good Corporate Governance consists of audit committee, the size the board of directors, the proportion of independent directors, and the number of board of commissioners. The research uses 12 samples in mining sector companies from 2015-2018 who did not have negative profit. The research sampling technique uses purposive sampling method while for data analysis uses multiple linear regression. The results show that the proxy committee variable proxy and the size of the board of directors have a significant effect on financial performance which is proxied by the ROE variable. As for the proxy variable, the proportion of independent directors and the number of board of commissioners do not significantly influence the financial performance that is proxied by ROE. Variable Corporate social responsibility index shows the results do not affect the financial performance which is proxied by the ROE variable. This research is important to be carried out as a study material for the mining industry on the importance of implementing GCG and CSR